Profil Kemampuan Pemahaman Konsep Ditinjau dari Kecemasan Matematis Siswa Smp pada Pembelajaran Tatap Muka Terbatas - Sandra Nindiani Suci; Asih Miatun (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
The aim of this study was to describe the profil in conceptual understanding abilities based on mathematical anxiety of junior high school students with limited face-to-face learning. A qualitative, descriptive method was used in this analysis. The subjects in this study were students in class VIII-H at SMPN 2 Cikarang Barat. The research subjects were six people, consisting of two people in each category of mathematical anxiety, selected by purposive sampling based on their mathematical anxiety to analyze their ability to understand mathematical concepts. This research used a mathematical concept understanding ability test, a mathematical anxiety questionnaire, and in-dept interviews. Data analysis methods include data presentation, data reduction, and drawing conclusions.The results reveal that students with low mathematical anxiety understand mathematical concepts better than students with medium or high mathematical anxiety. There are only two indicators of the mathematical concept understanding ability that are met by students with a high level of mathematical anxiety, namely: verbally conveying the concepts that have been taught and classifying objects based on certain forms that are similar to the concept requirements (showing examples and not examples). Students with medium levels of mathematical anxiety have three indicators of their mathematical concept understanding ability: verbally conveying the concepts that have been taught; classifying objects based on certain forms that are similar to the concept requirements (showing examples and not examples); and building necessary or sufficient conditions for a concept. Meanwhile, students with low mathematical anxiety almost fulfilled all indicators of mathematical concept understanding ability